Iberian Babel: Translation and Multilingualism in the Medieval and the Early Modern Mediterranean
1 online resource.
Keywords: "This book brings together translation and multilingualism, underlining their connection while addressing their evolving history in medieval and early modern Iberia and the Mediterranean. Herein lies its novelty and importance: bringing together translation and multilingualism and studying them from a trans-national point of view. Both translation and multilingualism are an integral part of Iberian culture and have shaped its literary traditions and cultural production for centuries, contributing to the transmission of knowledge and texts, and to the formation of the religious, linguistic, and ethnic identities that came to define medieval and early modern Iberia. Contributors are Jason Busic, John Dagenais, Emily C. Francomano, Marcelo E. Fuentes, Claire Gilbert, Roser Salicrú i Lluch, Anita J. Savo, and Noam Sienna"--